The Influence of New-Onset Atrial Fibrillation After Coronary Artery Bypass Grafting on Three-Year Survival - Rasco Sandy Sihombing; Muhadi Muhadi; Arif Mansjoer; Ikhwan Rinaldi (Interna Publishing, 2020)
Background: new-onset atrial fibrillation after coronary artery bypass grafting (CABG) is a common postoperative complication. This arrhytmia considered as temporary phenomenon which the majority are converted back to sinus rhytm when the patients discharged from the hospital. Despite its transience, those arrhytmia can recur and increasing the long term mortality. This study aims to determine the role of new-onset atrial fibrillation after CABG in three year survival. Methods: retrospective cohort study using survival analysis of patients who underwent coronary artery bypass grafting since January 2012 to December 2015 at Cipto Mangunkusumo Hospital. Patients with atrial fibrillation before surgery, who had surgery without cardiopulmonary bypass machine, and who died in 30 days after surgery are excluded. Subjects are divided into two category based of the presence of new-onset atrial fibrillation after CABG and the mortality status is followed up until 3 years post-surgery. The Kaplan-Meier curve is used to determine the three-year survival of the patients who had new-onset atrial fibrillation after CABG and Cox regression test used as multivariate analysis with confounding variables in order to get adjusted hazard ratio (HR). Results: new-onset atrial fibrillation after-CABG occurred in 29,59% patients. Patients with new-onset atrial fibrillation after CABG have higher three-year mortality (15,52% vs 3,62%) and significantly decreases three-year survival (p=0,008; HR 4,42; 95% CI 1,49-13,2). In multivariate analysis, new-onset atrial fibrillation after CABG is an independent factor of the three-year survival decline (adjusted HR 4,04; 95% CI; 1,34-12,14). Conclusion: new-onset atrial fibrillation after CABG independently decreases three-year survival.